Exploring Content Creators’ Language Learning Experiences and Multilingual Practices to Engage Audience in Instagram - Azzahro, Fitri Rahmadona; Silvhiany, Sary (Universitas Nurul Jadid, 2025)
The rise of digital technology has transformed communication and content creation, particularly on social media platforms like Instagram. This study explores how content creators use English and multimodal elements to engage audiences, the challenges they face, and how their English learning experiences influence their content creation practices. Using a qualitative approach, data were collected through semi-structured interviews with four Instagram content creators and an analysis of their digital artifacts. Findings reveal that content creators develop their English proficiency through formal education, self-learning via media exposure, and interactive digital communication. English is employed strategically to reach broader audiences, with creators combining it with their native language through code-switching. Multimodal elements, such as text, images, and audio, play a crucial role in enhancing engagement, enabling creators to convey messages effectively. Despite these advantages, challenges persist. Non-native English-speaking creators face difficulties in grammar accuracy, pronunciation, and vocabulary selection. To overcome these, they rely on tools like online dictionaries, AI-based applications, and audience feedback. The study also highlights that content creation fosters confidence in English use and enhances digital literacy skills. By examining the intersection of language learning, multimodal communication, and audience engagement, this research contributes to the understanding of English as a global language in digital spaces. The findings offer insights for educators, learners, and content creators seeking to navigate the evolving landscape of digital communication.